2006
DOI: 10.1080/03031853.2006.9523755
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic efficiency optimisation of alternative agricultural water use strategies

Abstract: Mathematical programming was used to optimise utility efficient deficit irrigation schedules for maize in Vaalharts, based on certainty equivalence assuming an exponential utility function. Total gross margin risk resulting from production risk of alternative deficit irrigation practices was quantified using an irrigation simulation model and stochastic budgeting procedures. Results showed that the portfolio of irrigation schedules for a risk averse farmer may include schedules with high production risk, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Comparing the SERF efficiency frontiers of alternative scenarios yield the utilityweighted risk premium that a decision-maker needs to be compensated for when moving from the preferred alternative to a less preferred alternative. Absolute risk-aversion coefficients were chosen to correspond to maximum plausible levels of risk aversion as determined by Grové (2008). The result showed that deficit irrigation is stochastically more efficient than full irrigation under limited water-supply conditions due to the larger areas irrigated.…”
Section: Intra-seasonal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the SERF efficiency frontiers of alternative scenarios yield the utilityweighted risk premium that a decision-maker needs to be compensated for when moving from the preferred alternative to a less preferred alternative. Absolute risk-aversion coefficients were chosen to correspond to maximum plausible levels of risk aversion as determined by Grové (2008). The result showed that deficit irrigation is stochastically more efficient than full irrigation under limited water-supply conditions due to the larger areas irrigated.…”
Section: Intra-seasonal Modelsmentioning
confidence: 99%
“…The modified SAPWAT model was used to simulate water use and crop-yield indices of 1 296 different irrigation schedules for 3 different states of nature included in the SAPWAT weather database. The crop-yield indices were combined with subjectively elicited crop-yield distributions to characterise the crop yield associated with different irrigation technologies (see Grové, 2008 for details). The generated data were used in an optimisation model to optimally allocate water between 3 crops.…”
Section: Intra-seasonal Modelsmentioning
confidence: 99%
“…It is easy to use the model because it is supplied with weather data and a unique set of crop parameters specific to South Africa. 17 In addition, the crop varieties database in SAPWAT is extensive and it has provision for tree and deciduous crops which is not common in other models. SAPWAT uses the Koppen climate system 18 for calculating crop coefficients and will therefore make it widely acceptable 14 .…”
Section: Sapwatmentioning
confidence: 99%
“…SWB is a crop growth simulation model that was specifically developed to improve real-time irrigation scheduling. 17 SWB adoption has been relatively slow and the user base is still very small because it is cumbersome to set up the model and to simulate predefined irrigation schedules.…”
Section: Impact Of Climate Change On Crop Water Requirementmentioning
confidence: 99%
“…The inclusion of risk in decision models under deficit irrigation has been proposed by some authors such as Grové (2006) who used efficient deficit irrigation schedules based on certainty equivalence assuming an exponential utility function, and Upendram et al (2015) who analysed a series of simulations of irrigated crop production in the Kansas High plains aquifer to identify the risk-efficient conditions. Both papers conclude that models on irrigation decision making should include risk into the objectives of the farmer.…”
Section: Introductionmentioning
confidence: 99%